The Community Prevalence of Vitamin C Deficiency and Inadequacy—How Does Australia Compare With Other Nations? A Scoping Review - Danielle M. Carter; Hiep N. Le; Hai Phung (Health Science Reports)
ABSTRACT Background and Aims Vitamin C is a vital nutrient for health and wellbeing and is essential for the prevention of and recovery from many conditions and diseases. This review aimed to map existing literature, identify knowledge gaps, and provide an overview of the community prevalence of vitamin C deficiency and inadequacy globally, based on serum levels. The Australian context is discussed in detail. Methods A systematic search using Scopus, PubMed, and CINAHL was conducted for articles reporting on prevalence rates of vitamin C deficiency and/or inadequacy, with serum vitamin C levels, published from 2003 to 2023. Studies including hospitalised patients were excluded. Results From 4842 unique studies identified, 107 met criteria for inclusion in the final review. Only 31 countries have conducted studies on community serum vitamin C levels in the last 20 years, with nationally representative studies lacking in all age groups, particularly in preschoolers, children, and adolescents (except for the US and Mexico). The prevalence of deficiency in high‐income countries is likely between 0% and 15%, with current reference ranges underestimating overall inadequacy for optimal health, by approximately 33.6%. Conclusions Australia and other nations around the world may have high levels of undetected vitamin C inadequacy which requires urgent investigation. Outdated reference ranges used for measuring serum vitamin C levels in Australia likely underestimate the prevalence of inadequacy. Serum vitamin C levels should be added as a biomarker to the next Australian Health Survey to assess community prevalence of deficiency and inadequacy. Screening guidelines for vitamin C deficiency and inadequacy should be established for use by Australian General Practitioners. The Australian Recommended Dietary Intake for vitamin C should be increased to align with levels that promote optimal health outcomes, rather than merely prevention of deficiency.